Searching for common deviations from South Africaﾒs Tax Treaty Policy: The relationship with North Africa, West Asia and Eastern Europe - Gordhan, Komil Dilap (Department of Finance and Tax, 2020)
To achieve a degree of standardisation of the contents of treaties by their members, Model tax conventions were published by international organisations. Consequently, in 1963, the Organisation for Economic Co-operation and Development (“OECD”) Model was prepared by developed countries of the world and it thus embodies rules and proposals by capital-exporting countries. As it was drafted by representatives of major Western industrialised countries, lower-income, developing countries were concerned that it resulted in too large a reduction in source country tax. The developing countries responded to the success of the OECD Model by developing their own Model convention under the auspices of the United Nations (“UN”) in 1980. This Model was drafted between developed and developing countries and attempts to reflect the interests of developing countries. Although it is based upon the OECD Model, the United Nations Model Double Taxation Convention between Developed and Developing Countries retains much greater source country taxation. Several tax treaties have been promulgated over time in South Africa due to the surge in international trade and investment flows which have tax consequences. There is however, no external enforcement of the above Models in the Republic of South Africa (“RSA”) and as a direct result, deviations from these standard models occur. Both a qualitative and expository study was performed. Thereafter, this dissertation considers South Africa’s treaty practice by outlining the significant deviations between South African double tax treaties and the respective OECD and UN Models. This study examines treaties concluded between South Africa and countries situated in North Africa, East Europe and West Asia. This dissertation concludes that bilateral treaties negotiated and concluded with South Africa consistently deviate from both the OECD and UN Models. These deviations were further examined to establish whether an indicative pattern informs a particular treaty practice. A small number of these observed deviations concur with the RSA position taken on the OECD Model. Treasury needs to circulate a clear and distinct South African Tax Model since South Africa’s international trade and investment flows expand across borders. The concern that South Africa does not have a published Tax Treaty Model is likely to intensify as related parties draw on frequently changing tax Models by the OECD and UN committees which may indirectly affect a developing country’s negotiating power.